2015
DOI: 10.1016/j.jphotobiol.2015.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Using hyperspectral imaging to determine germination of native Australian plant seeds

Abstract: a b s t r a c tWe investigated the ability to accurately and non-destructively determine the germination of three native Australian tree species, Acacia cowleana Tate (Fabaceae), Banksia prionotes L.F. (Proteaceae), and Corymbia calophylla (Lindl.) K.D. Hill & L.A.S. Johnson (Myrtaceae) based on hyperspectral imaging data. While similar studies have been conducted on agricultural and horticultural seeds, we are unaware of any published studies involving reflectance-based assessments of the germination of tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Such technologies are already in wide use in agriculture for such diverse applications as: (1) predicting seed germination (Nansen et al, 2015); (2) distinguishing between pest-infested and non-infested seeds (Nansen et al, 2014); (3) monitoring crop responses to biotic stressors (Prabhakar et al, 2012; Nansen and Elliott, 2016); (4) assessing the leaf area index (LAI) of wheat ( Triticum aestivum ) and potato ( Solanum tuberosum ) (Herrmann et al, 2011); and (5) determining – using near infrared (NIR) – rapeseed quality, i.e., seed weight and total oil content and oil fatty acid composition (Velasco et al, 1999). In addition, weed science studies have used hyperspectral methods to distinguish between weeds and crops (Okamoto et al, 2007; López-Granados et al, 2008; Herrmann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Such technologies are already in wide use in agriculture for such diverse applications as: (1) predicting seed germination (Nansen et al, 2015); (2) distinguishing between pest-infested and non-infested seeds (Nansen et al, 2014); (3) monitoring crop responses to biotic stressors (Prabhakar et al, 2012; Nansen and Elliott, 2016); (4) assessing the leaf area index (LAI) of wheat ( Triticum aestivum ) and potato ( Solanum tuberosum ) (Herrmann et al, 2011); and (5) determining – using near infrared (NIR) – rapeseed quality, i.e., seed weight and total oil content and oil fatty acid composition (Velasco et al, 1999). In addition, weed science studies have used hyperspectral methods to distinguish between weeds and crops (Okamoto et al, 2007; López-Granados et al, 2008; Herrmann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…27a). A study of seed germination (Nansen et al, 2015) using HSI showed that although viable and nonviable seeds appear identical to the human eye they can be clearly distinguished using full reflectance spectra (Fig. 27b).…”
Section: Hyper-spectral Imaging and Machine Learning For Real Time Emmentioning
confidence: 99%
“…Its use in data collection campaigns is becoming frequent in applications that range from agriculture, landscaping georeferencing, food processing, mineralogy to others such as surveillance and inspection tasks [13,32]. One of most promising field of application is precision agriculture, where hyperspectral imaging is used to collect data from seeds, and determine the germination of plant seeds [28]. Based on acquired information, the authors are able to detect significant changes in seed coat, responsible for the loss of germination.…”
Section: Hyperspectral Camerasmentioning
confidence: 99%
“…The huge increase in hyperspectral computational systems capacity, together with the reduction of their dimensions and weight, has encouraged its potential use in several domains such as: agriculture [28], industry [47], inspection [31] and surveillance [41]. Moreover, the development of novel computational methods and processors, some of them enabling parallel hardware/software implementations, thus more capable of processing the vast amount of generated data contributed to the increase hyperspectral cameras range of applications.…”
Section: Introductionmentioning
confidence: 99%